Pemanfaatan Digital Marketing Sebagai Upaya Peningkatan Penjualan Bagi UMKM di Plosokerep Kota Blitar - Lisma Rosmawati; Dewi Deniaty Sholihah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Plosokerep is one of the sub-districts in Blitar City which has the potential for various MSMEs, especially entrepreneurs and home industries. This business has become the livelihood of the people in Plosokerep Village, Sananwetan District, Blitar City. In Plosokerep District itself, many MSMEs are innovating in opening their businesses but are not maximizing the potential of social media as one of their markets. Fahmi Jaya Kue, namely the use of the brand has not been maximized, even though it has been around for a long time and has received many orders from consumers. Small, medium and micro businesses pay little attention to the use of social media to promote Fahmi Jaya Kue's business, so that Fahmi Jaya Kue's regular customers are few, and product marketing has not expanded. product brand knowledge. Therefore, the people around Blitar City, especially Plosokerep Village, do not yet have many products and brands from small, medium and micro businesses that are known by the village community. All one has to do is create social media, marketplace and website.